Kegiatan Lomba Menggambar dan Mewarnai Tingkat SD Se-Desa Petak - I Ketut Sutapa; I Made Bayu Wisnawa; Luh Komang Candra Dewi; Gde Herry Sugiarto Asana; Dewiwati Sujadi; Made Christin Dwitrayani; I Dewa Ayu Tita Permata Tabita; Kadek Dwik Ariasih; Luh Septiani Ulandari; I Wayan Gede Widiyantara; I Putu Kesuma Yuda (Prosiding Seminar Nasional Riset dan Pengabdian pada Masyarakat, 2024)
This research examines coloring and drawing competitions. Drawing and coloring competitions are activities that have a positive impact on the development of creativity and artistic talent in children. This competition is not only an opportunity to express oneself artistically, but also prioritizes collaboration, healthy competition and appreciation of fine arts. Fine arts plays an important role in children's development because it provides opportunities for them to express themselves, develop creative skills and strengthen the teaching and learning process. The research location was in Banjar Madangan Kaja which was carried out on February 12 2024. Data collection techniques were carried out using observation, interviews and documentation. The research results show that the majority of elementary school students in Petak Village have high creativity and enthusiasm in participating in drawing and coloring competitions. However, the problem experienced when this competition was held was that the participants who took part in the competition did not arrive on time, therefore the committee carried out a follow-up with the principal of the SDN school in Petak Village.